Education As An Effort To Increase Public Awareness Of Leprosy Through The Health Promotion Program Of The Health Center, Dermatology Polyclinic, Muhammadiyah Hospital, Lamongan - Enik Srihartati; Sofyan Azhari Dimya Putra; Aringga Yusuf Amrullah; Rosyinaafi Rudie Al Mahdi; Asra Zahra Asdi; Raisa Jehan Fawwazie; Qonita Aulianisa Isfahanni (DokTIn MEDIKA Jurnal Pengabdian Masyarakat, 2024)
Introduction: Leprosy remains a communicable disease that can cause permanent disability if not detected and treated early. Low community literacy about leprosy, particularly in primary health care settings such as Brondong Health Center, poses a major challenge. This community service program aimed to increase public awareness and knowledge regarding risk factors, signs and symptoms, and the importance of early detection of leprosy. Methods: The program applied a Service Learning (SL) approach, conducted directly at Brondong Health Center. Activities included interactive health education using presentations, educational videos, question-and-answer sessions, quizzes, and distribution of educational leaflets and posters. Evaluation was carried out using standardized pretest and posttest questionnaires. Result: The program showed an increase in participants’ knowledge scores, with the majority achieving at least a 50% improvement from pretest to posttest. Participants demonstrated higher awareness of leprosy symptoms and risk factors, as well as a positive response toward routine skin and nerve examinations. Conclusion: Community-based structured education through health promotion activities effectively improved public knowledge and awareness regarding leprosy. Such interventions play an important role in reducing delayed diagnosis and preventing disability in affected individuals. Keywords: Leprosy, Health Education, Community Awareness, Early Detection, Service Learning